Outcomes of surgical treatment on type A acute aortic dissection accompanied with coronary artery involvement - Qin, Wei; Fan, Rui; Wang, Jiankai; Li, Jian; Huang, Fuhua; Chen, Xin (Frontiers in Surgery, 2022)
Background: Coronary artery (CA) involvement due to acute aortic dissection (AAD) is a catastrophic cardiovascular disease with high mortality. Two main surgery strategies, local coronary repair and coronary artery bypass grafting (CABG) can be applied to reestablish the blood flow in the aortic repair. This study was to evaluate the operative and long-term outcomes of type A AAD patients, who received aortic dissection repair plus CABG or local coronary repair. Method: We reviewed our database and screened 148 type A AAD patients with CA involvement from January 2001 to December 2021. Local coronary repair or CABG was performed concomitantly on these enrolled patients. Results: At the time of aortic repair, there were 58 patients with concomitant CABG (Group I) and 90 patients with local coronary repair (Group II). The basal characteristics of these two groups had no difference, except for acute myocardial ischemia (AMI) and CA involvement type. 45 patients with AMI in Group I, but none in Group II (P <0.001). There was a higher frequency of type B and C lesions of CA involvement in Group I than that in Group II (P <0.001). There was no difference in surgical procedures and complications, except for postoperative acute kidney injury (AKI) (34.5% vs. 8.9%, P <0.001). Hospital mortality in Group I was higher than that in Group II, but without statistical difference (20.7% vs. 11.1%, P =0.155). No significant difference was obtained in long-term survival rate between the two groups ( 82.5±4.8% vs. 81.2±6.9%, P =0.19). Conclusion: CABG and local coronary repair suits different types of CA involvement, and their effects on perioperative results and long-term survival for type A AAD patients with CA involvement are equal.